2008
DOI: 10.1007/s00432-008-0502-3
|View full text |Cite
|
Sign up to set email alerts
|

Splenic metastases—not a frequent problem, but an underestimate location of metastases: epidemiology and course

Abstract: The published studies of the frequency of the splenic metastasis are autopsy studies, which are not usable for epidemiological statements because of selection bias. We show that splenic metastases arise in less than 1% of all metastases. A splenectomy in case of splenic metastases makes sense, if the metastases are isolated. It is also meaningful as a debulking procedure that would be followed by a chemotherapy, e.g. in case of an ovarial carcinoma. As a result the survival is increased for patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 8 publications
1
50
0
3
Order By: Relevance
“…After ablation, complete necrosis was obtained, and the post-ablation survival (mean 22 months) for the four patients is comparable to that of splenectomy treatment as the published studies reported [21,22]: the median survival 11-19.5 months. Noticeably, in order to avoid the potential risks, several important steps should be followed: (1) the high vascularisation of the spleen produces extremely high intra-abdominal temperature with the risk of thermal injury of the adjacent viscera.…”
Section: Discussionsupporting
confidence: 66%
“…After ablation, complete necrosis was obtained, and the post-ablation survival (mean 22 months) for the four patients is comparable to that of splenectomy treatment as the published studies reported [21,22]: the median survival 11-19.5 months. Noticeably, in order to avoid the potential risks, several important steps should be followed: (1) the high vascularisation of the spleen produces extremely high intra-abdominal temperature with the risk of thermal injury of the adjacent viscera.…”
Section: Discussionsupporting
confidence: 66%
“…Another very recent study found only 59 patients with splenic metastases from a total of 29364 patients with malignant tumors. Only three patients had isolated splenic metastasis from non-colorectal primaries [2].…”
Section: Discussionmentioning
confidence: 99%
“…Splenic metastases arise in less than 1% of all metastases [2], and their most common primary sources are breast, lung, colorectal, and ovarian carcinomas in cases of multivisceral cancer [3]. Isolated solitary splenic metastases from colorectal carcinoma are a very rare clinical entity despite the fact that the spleen is the largest single mass of lymphoid tissue in the body [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Ugotovili so, da se je pri splenektomiranih bolnikih, pri katerih je bil namen kirurškega zdravljenja ozdravitev, preživetje podaljšalo in je srednje preživetje znašalo 20 mesecev, v skupini, ki je bila operirana z namenom blažitve težav, pa je srednje preživetje znašalo le 5 mesecev.5 Prav tako o podaljšanem preži-vetju poročajo študije, ki so preučevale vpliv metastazektomije na preživetje pri bolnikih z izoliranimi metastastkimi melanomskimi spremembami v drugih organih (pljuča, GIT in drugi visceralni organi).11,20,22-25 Podaljšano preživetje so opažali tudi pri bolnikih, ki so jim odstranili vranico zaradi metastaz karcinomov drugih solidnih organov. 26 Splenektomija je pri metastazah v vranici na mestu predvsem z namenom blaži-ti simptome in izboljšati kakovost življenja oziroma v primeru rupture vranice za preprečitev takojšnje smrti.5 Pri dokazanih izoliranih metastatskih spremembah v vranici je operacija lahko metoda zdravljenja, ki pomembno podaljša preživetje pri bolnikih z metastatsko boleznijo.5 Po podatkih iz literature je bila, tako kot v našem primeru, pri večini bolnikov opravljena klasična odstranitev vranice z laparotomijo.5,6 V literaturi Klinični priMer/Case report pa se že pojavljajo posamezni primeri, ko so metastatsko infiltrirano vranico odstranili laparoskopsko.19…”
Section: Razpravljanjeunclassified